Histoplasmosis-Induced Hemophagocytic Syndrome: A Case Series and Review of the Literature. (15th April 2015) - Townsend, Jennifer Leigh; Shanbhag, Satish; Hancock, John; Bowman, Kathryn; Nijhawan, Ank E.
Abstract: Background.  Histoplasmosis-associated hemophagocytic lymphohistiocytosis (HLH) is a relatively rare disorder for which data are limited regarding optimal treatment and clinical outcomes in adults. We describe the clinical features, treatment, and outcomes of patients with histoplasmosis-associated HLH at our institution. Methods.  We performed a retrospective chart review of all inpatients at Parkland Hospital diagnosed with HLH associated with Histoplasma capsulatum from 2003 to 2013. Results.  Eleven cases of histoplasmosis-associated HLH over this time period were identified. Nine of eleven cases were males (82%). Nine of these patients had human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS), 1 was a renal transplant patient on immunosuppressants, and the other had no documented immunocompromise. The most common HLH criteria were splenomegaly (n = 10), fever (n = 10), and ferritin >500 ng/dL (n = 9). Urine Histoplasma antigen was positive in every patient tested (n = 9 of 9), and most antibodies for Histoplasma were positive if checked (n = 4 of 5). A majority of patients received liposomal amphotericin B (n = 9) with an average treatment duration of 11 days, and 5 patients also received prednisone, intravenous immunoglobulin (IVIG), or both. Overall, 5 patients died within 30 days (45.5%), and 7 patients died within 90 days (63.6%). Of the 5 patients that received immunosuppression, 4 died (80%), whereas in the group not given additional immunosuppression (n = 5), 2 died (40%). Conclusions.  Histoplasmosis-associated HLH among adults is a lethal disease of highly immunocompromised patients, especially patients with HIV/AIDS. Clinical features such as splenomegaly, elevated ferritin, and cytopenias should prompt evaluation for HLH in this population. Further data are needed to define the role of immunosuppression, IVIG, and highly active antiretroviral therapy in treating this condition.